2
votes
3answers
45 views

Fibonacci Sequence, Golden Ratio

I've been asked to show that $x_n \rightarrow L$ as $n \rightarrow \infty$ where $x_n = F_{n+1}/F_{n}$ for $n \in \mathbb{Z}^+$, where $F_n$ denotes the $n^{th}$ Fibonacci number. I am supposed to use ...
5
votes
3answers
923 views

Fibonacci trick and proving it. [duplicate]

I am trying to learn Fibonacci tricks and I have one that I can not prove. I know it works because Ive tried it multiple times but I have not a clue how to prove. Here it is: ...
0
votes
1answer
33 views

Fibonacci Proof with Induction [duplicate]

$$f(n) = \left\{\begin{matrix} 0 & n=1\\ 1 & n=2\\ f_{n-1} + f_{n-2} & n\geqslant 2\end{matrix}\right.$$ How can I prove by induction that $$f_{n} \geq \left ( 1.5 \right )^{n-1}$$ ...
2
votes
2answers
45 views

Fibonacci Proof Using Induction

$$f(n) = \left\{\begin{matrix} 0 & n=1\\ 1 & n=2\\ f_{n-1} + f_{n-2} & n\geqslant 2\end{matrix}\right.$$ How can I prove by induction that $$f_{n} \leq \left ( \frac{1+\sqrt{5}}{2} ...
0
votes
2answers
82 views

Proving that $fib(n) < (5/3)^n$ for $n \ge 1$ by induction

I know this has been shown before here but no post really answered my question. I had this problem given to me as an induction practice problem and I couldn't solve it without help. When I got the ...
6
votes
3answers
177 views

Is there a proof for this Fibonacci relationship?

I was looking at the decomposition of Fibonacci numbers using the definition of $F_n = F_{n-1} + F_{n-2}$, and noted the pattern in the coefficients of the terms were Fibonacci numbers. It appears to ...
2
votes
1answer
171 views

How do I use telescopic cancellation to prove the Fibonacci Sum Identity

I am reading a textbook which attempts to prove the Fibonacci Sum Identity by rearranging the Fibonacci recurrence relation as follows and then using telescoping cancellation to prove the identity: ...
2
votes
2answers
629 views

Solve the recurrence of $T(n)= 3T(n-1)+1$ with$ T(0)=2$ by iteration of the recurrence

Solve the recurrence of $T(n)= 3T(n-1)+1$ with $T(0)=2$ by iteration of the recurrence. (I was told that there is no need to prove it by induction) I googled "iteration of the recurrence." I did not ...
0
votes
0answers
23 views

Solve the recurrence of T(n)= 3T(n-1)+1 with T(0)=2 as a first order linear recurrence. [duplicate]

Solve the recurrence of T(n)= 3T(n-1)+1 with T(0)=2 as a first order linear occurrence. I would do T(0)= 3T(-1)+1=2. I need to find a condition for n<0 and n>0. Any tips on getting started? ...
1
vote
2answers
107 views

Suppose that a recursive routine were invoked to calculate F(4). How many times would a recursive call of F(1) occur?

The definition of a Fibonacci number is as follows: $$F_0=0\\F_1=1\\F_n=F_{n-1}+F_{n-2}\text{ for } n\geq 2$$ Suppose that a recursive routine were invoked to calculate $F_4$. How many times would a ...
1
vote
3answers
484 views

Prove that $F(n+3)=2F(n+1)+ F(n)$ for $n \ge 0$

The definition of a Fibonacci number is as follows: $$F(0)=0\\ F(1)=1\\ F(n)= F(n-2)+F(n-1)\text{ for }n\geq 2$$ Prove the given property of the Fibonacci numbers directly from the definition. ...
2
votes
2answers
365 views

How do I prove Binet's Formula? [duplicate]

My initial prompt is as follows: For $F_{0}=1$, $F_{1}=1$, and for $n\geq 1$, $F_{n+1}=F_{n}+F_{n-1}$. Prove for all $n\in \mathbb{N}$: ...
1
vote
2answers
364 views

proof by induction to demonstrate all even Fibonacci numbers have indices divisible by 3

I am practicing proof by induction, and would like to use induction to prove the following hypothesis about the Fibonacci numbers: $$(\forall n\ge0) \space 0\equiv n\space mod \space 3 \iff 0 \equiv ...
1
vote
2answers
120 views

Induction on the Fibonacci sequence?

Prove by induction that the $i$th Fibonacci number satisfies the equality: $$F_i = \frac {\phi^i - \hat\phi{}^i}{\sqrt5}$$ where $\phi$ is the golden ratio and $\hat\phi$ is its conjugate. ...
7
votes
7answers
534 views

Prove the following equality: $\sum_{k=0}^n\binom {n-k }{k} = F_n$ [duplicate]

I need to prove that there is the following equality: $$ \sum\limits_{k=0}^n {n-k \choose k} = F_{n} $$ where $F_{n}$ is a n-th Fibonacci number. The problem seems easy but I can't find the way to ...
4
votes
1answer
216 views

prove that $\operatorname{fib}(n)<{(5/3)}^n$

I am trying to prove that $$ \operatorname{fib}(n)<\left(\frac{5}{3}\right)^n $$ where $\operatorname{fib}(n)$ is the $n^{th}$ fibonacci number. For a proof I used induction, as we know ...